Prevention Turn Over Strategy: Analysis Recuitment, Career Development, Work Environment, Capability Information Technology, and Reward System - Jumawan (East Asian Journal of Multidisciplinary Research, 2023)
The results of the literature review above are many factors that cause turnover to occur in The purpose of this study is to determine the factors that influence turnover strategies in companies, as for factors that are significant or insignificant, it can be seen from the synthesis in this article, the findings are several factors are the main causes so that employees do not resign from the company, the research method of this article is a literature review that does not have respondents and for the literature review is a mixture of national and international articles.